2022
DOI: 10.1155/2022/1337588
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Magnetite/Hydroxyapatite: A Green Nanocomposite for T2-Weighted MRI and Curcumin Carrying

Abstract: Background. The design of new magnetic resonance imaging (MRI) contrast media with chemotherapy drug-carrying capacity has an important role in diagnostic and therapeutic purposes. This study aimed to synthesize a polyethylene glycol (PEG)-coated magnetite/hydroxyapatite nanocomposite as an MRI contrast agent investigate its curcumin loading/release properties and consider the cytotoxicity effect of the curcumin-loaded nanocomposite on different cell lines. Materials and Methods. PEGylated magnetite/hydroxyapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Due to the above-mentioned risks, and since some studies have shown that bare MNP are more toxic compared to coated NP due to the existence of more available oxidative sites that promote ROS production, [158,162,165,167] surface coatings of shells have been suggested in the development of MNP for bone TE applications, aiming at biocompatibility and nontoxicity. [58,[170][171][172] Coatings such as natural polysaccharides, [173][174][175][176][177] polymer materials, [178][179][180][181][182][183][184] noble metals, [185][186][187][188][189][190] or inorganic materials such as bioceramics [57,58,171,[191][192][193][194][195][196] are widely reported and suggested. Therefore, due to the vast diversity of factors that must be taken into consideration when assessing the toxicity of MNP, it is challenging to assign a clear/definite toxicity profile that can be followed when choosing the proper MNP for the intended applications.…”
Section: Toxicity and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the above-mentioned risks, and since some studies have shown that bare MNP are more toxic compared to coated NP due to the existence of more available oxidative sites that promote ROS production, [158,162,165,167] surface coatings of shells have been suggested in the development of MNP for bone TE applications, aiming at biocompatibility and nontoxicity. [58,[170][171][172] Coatings such as natural polysaccharides, [173][174][175][176][177] polymer materials, [178][179][180][181][182][183][184] noble metals, [185][186][187][188][189][190] or inorganic materials such as bioceramics [57,58,171,[191][192][193][194][195][196] are widely reported and suggested. Therefore, due to the vast diversity of factors that must be taken into consideration when assessing the toxicity of MNP, it is challenging to assign a clear/definite toxicity profile that can be followed when choosing the proper MNP for the intended applications.…”
Section: Toxicity and Limitationsmentioning
confidence: 99%
“…[52,57,60,63,139,155,202,[205][206][207][208][209][210][211] By combining the biocompatible and bioactive properties of hydroxyapatite (HA) with the magnetic properties of pure magnetite, it is possible to obtain Fe 3 O 4 /HA core-shell NP of increased therapeutic value and with a greater application potential as a suitable platform for the construction of multifunctional and bimodal magnetic-theranostic carriers, for clinical oncology and novel MRI contrast agents. [57,58,174,177,179,212,213] However, it should be kept in mind that the formed shell may have a thickness greater than the core size, which may result in the decrease of the saturation magnetization of the magnetic material. [58] Since it is difficult to control the thickness of the HA layer, the current challenge in this research field involves the optimization of different HA synthesis routes to obtain a stable and thin shell surrounding the magnetite core.…”
Section: Calcium Phosphate-based Particles With Intrinsic Magnetic Pr...mentioning
confidence: 99%
“…The reported drug loading capacity was 1.9 mg/g and the r2 relaxivity was measured as 120 mM −1 S −1 . Antitumoral activity of the system was proven on A549 human alveolar adenocarcinoma cells and MCF-7 breast cancer cells [ 155 ].…”
Section: Hap For Cancer Detection and Cell Imagingmentioning
confidence: 99%